Complications associated with paediatric airway management during the COVID‐19 pandemic: an international, multicentre, observational study. (23rd March 2022) - Peterson, M. B.; Gurnaney, H. G.; Disma, N.; Matava, C.; Jagannathan, N.; Stein, M. L.; Liu, H.; Kovatsis, P. G.; von Ungern‐Sternberg, B. S.; Fiadjoe, J. E.; ,
Summary: Respiratory adverse events in adults with COVID‐19 undergoing general anaesthesia can be life‐threatening. However, there remains a knowledge gap about respiratory adverse events in children with COVID‐19. We created an international observational registry to collect airway management outcomes in children with COVID‐19 who were having a general anaesthetic. We hypothesised that children with confirmed or suspected COVID‐19 would experience more hypoxaemia and complications than those without. Between 3 April 2020 and 1 November 2020, 78 international centres participated. In phase 1, centres collected outcomes on all children (age ≤ 18 y) having a general anaesthetic for 2 consecutive weeks. In phase 2, centres recorded outcomes for children with test‐confirmed or suspected COVID‐19 (based on symptoms) having a general anaesthetic. We did not study children whose tracheas were already intubated. The primary outcome was the incidence of hypoxaemia during airway management. Secondary outcomes included: incidence of other complications; and first‐pass success rate for tracheal intubation. In total, 7896 children were analysed (7567 COVID‐19 negative and 329 confirmed or presumed COVID‐19 positive). The incidence of hypoxaemia during airway management was greater in children who were COVID‐19 positive (24 out of 329 (7%) vs. 214 out of 7567 (3%); OR 2.70 (95%CI 1.70–4.10)). Children who had symptoms of COVID‐19 had a higher incidence of hypoxaemia compared with those who were asymptomatic (9 out of 51 (19%) vs. 14 out of 258 (5%), respectively; OR 3.7 (95%CI 1.5–9.1)). Children with confirmed or presumed COVID‐19 have an increased risk of hypoxaemia during airway management in conjunction with general anaesthesia.